Kärlekssånger - en täckmantel för förbjudna begär - A Karlsson, Katarina (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2017)
Love is the most common theme in songs of all ages. But love is and has always been a cloak under which power, threats and pursuit are performed, and it can also ventriloquy illicit desires. In this article I will argue that love songs with female personas can have been used to express same-sex desire in the aristocratic, male, homo social coteries of the early modern England, while the majority of the Elizabethan love songs, those with male personas, often use the same rhetoric as that of a perpetrator of woman battering. The article also shows how the bodily perception of singing the songs reveals information which remain hidden to a reader.